Unionization Structure, Licensing and Innovation - Arijit Mukherjee; Enrico Pennings (Tinbergen Institute, 2005)
Taking technological differences between firms as given, we show that the technologically advanced firm has a stronger incentive for technology licensing under a decentralized unionization structure than with centralized wage setting. Furthermore, We show that, in presence of licensing, the incentive for innovation may also be stronger under decentralized unions. Unions have a clear preference for centralization only if productivity improvements are relatively small.
Keywords: D43; L13; O34; 330; Licensing; downstream market; upstream market; innovation; welfare